An investigation of the neural circuits underlying reaching and reach-to-grasp movements: from planning to execution - Begliomini, Chiara; De Sanctis, Teresa; Marangon, Mattia; Tarantino, Vincenza; Sartori, Luisa; Miotto, Diego; Motta, Raffaella; Stramare, Roberto; Castiello, Umberto (Frontiers in Human Neuroscience, 2014)
Experimental evidence suggests the existence of a sophisticated brain circuit specifically dedicated to reach-to-grasp planning and execution, both in human and non human primates (Castiello, 2005). Studies accomplished by means of neuroimaging techniques suggest the hypothesis of a dichotomy between a “reach-to-grasp” circuit, involving the intraparietal area (AIP), the dorsal and ventral premotor cortices (PMd and PMv - Castiello and Begliomini, 2008; Filimon, 2010) and a “reaching” circuit involving the medial intraparietal area (mIP) and the Superior Parieto-Occipital Cortex (SPOC) (Culham et al., 2006). However, the time course characterizing the involvement of these regions during the planning and execution of these two types of movements has yet to be delineated. A functional magnetic resonance imaging (fMRI) study has been conducted, including reach-to grasp and reaching only movements, performed towards either a small or a large stimulus, and Finite Impulse Response model (FIR - Henson, 2003) was adopted to monitor activation patterns from stimulus onset for a time window of 10 seconds duration. Data analysis focused on brain regions belonging either to the reaching or to the grasping network, as suggested by Castiello & Begliomini (2008). Results suggest that reaching and grasping movements planning and execution might share a common brain network, providing further confirmation to the idea that the neural underpinnings of reaching and grasping may overlap in both spatial and temporal terms (Verhagen et al., 2013).